Determinant Factors in Receiving Going Concern Audit Opinions - Rina Aprilyanti; Surachmat Wijaya (eCo-Fin, 2019)
The aims of this study is to determine whether or not there is (1)Impact of the Sustainability Report (SR) and company’s size towards acceptance of opinions going concern, (2) The Sustainability Report (SR) is categorized into three different dimensional disclosures based on guidelines made by the Global Reporting Initiative (GRI) that is The G4 Guidelines, with the Division of Economic Dimension (X1), environmental Dimension (X2) and social Dimension (X3) and (4) size of the company in the company's total assets (X4). The Sustainability report (Sustainability Report) is becoming a highlight and the need for progressive companies to inform about their economic, social and environmental performance as well as to all stakeholders of the company. In this study, data analysis used descriptive statistical analysis and hypothesis testing using a logistic regression analysis method, sample determination in this study is using a purposive sampling method as much as 10 companies with a total of 30 samples from the year 2014 – 2016 used as research data. Results showed that a partial disclosure of economic dimensions, environmental dimensions and social dimensions in the Sustainability Report and the size of the company had no significant influence on the company's financial performance, so the results were rejected. In-depth discussions and data analysis using linear logistical regression, the conclusion that the disclosure of economic dimension variables, environmental dimensions, and social dimension and company size have no significant effect on Acceptance opinion going concern